Implementasi Terapi Relaksasi Benson Terhadap Nyeri Akut Pada Pasien Dismenore - Mei Lestari Ika Widyyati; Ahmadi; Sri Alivia Damayanti (Indonesian Health Science Journal, 2025)
Background: Menstruation causes the uterine muscles to contract, causing pain in the lower abdomen, waist, and even back. Benson relaxation is given to patients who experience pain. The aim of this case study is to describe nursing care by providing Benson relaxation to reduce pain in Dismenore clients. Method: This writing method uses a descriptive method with a nursing process approach consisting of assessment, diagnosis, planning, implementation and evaluation. In the case study there are 2 clients with acute pain nursing problems in Dismenore patients. Implementation Results: The study was conducted in the Camplong Health Center Working Area, Sampang Regency by providing Benson relaxation therapy to respondents 3 times. The results of the study showed that on the 3rd day, Ms. A obtained data, pain complaints on a pain scale of 0 (no pain), appeared to be grimacing (decreased), and restless (decreased), with the interpretation of the problem being resolved. Ms. M as the second respondent showed data on pain complaints on a pain scale of 0 (no pain), appeared to be grimacing (decreased), and restless (decreased), with the interpretation of the problem being resolved. Conclusion: After providing nursing care with the implementation of Benson Relaxation Therapy to 2 clients, it can be concluded that the implementation of Benson Relaxation Therapy was proven to be effective in reducing acute pain.